Bidirectional self-locked energy absorbing system: Design and quasi-static compression properties. (November 2019) - Zhao, Yang; Chen, Liming; Du, Bing; Liu, Houchang; Chen, Baocai; Peng, Shiwei; Guo, Yongguang; Chen, Liliang; Li, Weiguo; Fang, Daining
Abstract: Thin-walled tubes are widely utilized as energy absorption element. It is necessary to realize the bidirectional self-locked of thin-walled tube system without any constraint under lateral and oblique impact for emergency protection and improving energy absorption. In this study, we designed a novel 3D printed thin-walled tube with variable section achieving rapid assembly of bidirectional self-locked thin-walled system. Comparison among the thin-walled tube with variable section, dumbbell-shaped tube, rectangular-shaped tube and three corresponding systems were conducted with regard to deformation and energy absorption. The typical deformation modes of three kinds of tube and system were obtained by experimental results. Oblique quasi-static compression tests were conducted to validate the bidirectional self-locked effect of system. Geometrical restriction satisfying bidirectional self-locked effect and parametric analysis of presented tube is discussed. It was found that specific energy absorption of the presented thin-walled tube with variable section is superior to these of dumbbell-shaped configuration and rectangular-shaped configuration from both perspectives of tube and system. Highlights: A novel bidirectional self-locked system is proposed. The typical deformation mode of three kinds of tube and system is discovered under quasi-static compression test. Condition of achieving bidirectional self-locked effect of system is given, and its parametric analysis is conducted by finite element. Energy absorption of bidirectional self-locked system is superior to other horizontal self-locked system.